Pengaruh Investment Opportunity Set, Pertumbuhan Perusahaan Dan Profitabilitas Terhadap Nilai Perusahaan - Srirahayu Wulanningsih; Henri Agustin (Universitas Negeri Padang, 2020)
This study was to analyze the Investment Opportunity Set (IOS), Growth, Profitability on firm value. The research object was the entire industrial sector of used in this study are annual reports in property and real estate companies on the indonesia stock exchange (idx) in the period 2014-2018. The method of taking data samples using purposive sampling method based on certain criteria. Based on the retrieval method obtained a sample of 36 companies. Hypothesis testing in this study uses multiple linear regression analysis. The results show that Investment Opportunity Set (IOS), Profitability have a positive influence on firm value and Growth has no influence on firm value.